2020
DOI: 10.1111/jam.14852
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus‐fermented milk products attenuate bone loss in an experimental rat model of ovariectomy‐induced post‐menopausal primary osteoporosis

Abstract: Aim In this study, we investigated the anti‐osteoporotic effect of two fermented milk products (FMPs) fermented by Lactobacillus plantarum A41 and Lactobacillus fermentum SRK414 on a rat model of ovariectomy‐induced post‐menopausal primary osteoporosis. Methods and Results The two Lactobacillus FMPs increased the bone volume and bone mineral density (BMD) in ovariectomized (OVX) rats, and normalized the bone biomarkers in the serum. Additionally, they altered the gene expression levels of bone‐metabolism‐relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 88 publications
2
27
0
Order By: Relevance
“…Zhou and colleagues reported that Lactobacillus rhamnosus GG (LGG) prevented excessive bone resorption by inhibiting the expression of IL-17 and RANKL in bone marrow [48]. Kim and colleagues showed that Lactobacillus-fermented milk alleviated bone loss by reducing the production of the pro-inflammatory cytokines TNFα and IL-1 [49]. Similar to our results, AR281 exhibited Data Availability Statement: RAW264.7 cell line was obtained from BeNa Culture Collection (No.…”
Section: Discussionsupporting
confidence: 82%
“…Zhou and colleagues reported that Lactobacillus rhamnosus GG (LGG) prevented excessive bone resorption by inhibiting the expression of IL-17 and RANKL in bone marrow [48]. Kim and colleagues showed that Lactobacillus-fermented milk alleviated bone loss by reducing the production of the pro-inflammatory cytokines TNFα and IL-1 [49]. Similar to our results, AR281 exhibited Data Availability Statement: RAW264.7 cell line was obtained from BeNa Culture Collection (No.…”
Section: Discussionsupporting
confidence: 82%
“…A clinical trial has determined the bone-protective effects of L. reuteri 6475 in older women with low bone mass ( 45 ). The intake of milk products fermented by L. plantarum A41, Lactobacillus fermentum SRK414, Lactobacillus paracasei NTU 101, or L. plantarum NTU 102 also increases bone mass in OVX rats ( 46 , 47 ). However, there are no reports on the role of Lactobacillus species in the maintenance of bone homeostasis in the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…After excluding differences related to BMI and medications, the study suggested an adverse effect of Lactobacillus on osteoporosis (Das et al, 2019). In contrast, part of Lactobacillus belonging to this genera, such as Lactobacillus acidophilus, Lacticaseibacillus paracasei GMNL-653, and Lactobacillus reuteri et al, were thought to positively regulate bone health (Dar et al, 2018;Lee et al, 2021;Jhong et al, 2022). Britton et al showed that Lactobacillus reuteri suppressed ovariectomyinduced increases in bone marrow CD4+ T lymphocytes and inhibited estrogen deficiency-induced bone resorption and bone loss (Britton et al, 2014).A study using a mouse model with gut microbial dysbiosis after antibiotic treatment found that Lactobacillus reuteri prevented osteoblastopenia and increased osteoclast activity, thereby preventing trabecular bone loss in the femur and spine and exerting a positive skeletal effect.…”
Section: Firmicutesmentioning
confidence: 99%
“…After excluding differences related to BMI and medications, the study suggested an adverse effect of Lactobacillus on osteoporosis ( Das et al., 2019 ). In contrast, part of Lactobacillus belonging to this genera, such as Lactobacillus acidophilus, Lacticaseibacillus paracasei GMNL-653, and Lactobacillus reuteri et al, were thought to positively regulate bone health ( Dar et al., 2018 ; Lee et al., 2021 ; Jhong et al., 2022 ). Britton et al.…”
Section: Intestinal Microbiota Classification Characteristics and Bon...mentioning
confidence: 99%